The Influence of The Effectiveness of Entrepreneurship Education and Soft Skills on Entrepreneurial Intentions Through the Skills Provision Program on High School Students in Pasuruan District - Sriarianie, Sriarianie; Nasikh, Nasikh; Hermawan, Agus (Journal of Applied Business, Taxation and Economics Research, 2024)
This study intends to analyze the direct effect and indirect effects of the effectiveness of entrepreneurship education and soft skills on entrepreneurial intentions mediated by the skills provision program (double track) in high school students in Pasuruan Regency. This study uses an explanatory research design (explanatory research) with a type of quantitative description analysis approach. The sample of this study was 198 out of 405 students of SMA Negeri 1 Gondangwetan and SMA Ma'arif NU Pandaan in Pasuruan Regency who participated in the skills provision program (Double Track) and data analysis was carried out using the Partial Least Square (PLS) method. The results showed that there is a positive and significant influence between entrepreneurship education on skills provision program (double track), there is a positive and significant influence between soft skills on double track program, there is a positive and significant influence between entrepreneurship education on entrepreneurial intention, there is a positive and significant influence between soft skills on entrepreneurial intention, there is a positive and significant influence between skills provision program (double track) on entrepreneurial intention in high school students in Pasuruan Regency. Skills Debriefing Program (Double track) mediates the relationship between Entrepreneurship Education with Entrepreneurial Intention, Skills Debriefing Program (Double track) mediates the relationship between Soft Skills with Entrepreneurial Intention